Few Associations Found between Mold and Other Allergen Concentrations in the Home versus Skin Sensitivity from Children with Asthma after Hurricane Katrina in the Head-Off Environmental Asthma in Louisiana Study. (6th December 2012) - Grimsley, L. F.; Wildfire, J.; Lichtveld, M.; Kennedy, S.; El-Dahr, J. M.; Chulada, P. C.; Cohn, R.; Mitchell, H.; Thornton, E.; Mvula, M.; Sterling, Y.; Martin, W.; et al.
Abstract : Mold and other allergen exposures exacerbate asthma symptoms in sensitized individuals. We evaluated allergen concentrations, skin test sensitivities, and asthma morbidity for 182 children, aged 4–12 years, with moderate to severe asthma, enrolled 18 months after Katrina, from the city of New Orleans and the surrounding parishes that were impacted by the storm, into the Head-off Environmental Asthma in Louisiana (HEAL) observational study. Dust (indoor) and air (indoor and outdoor) samples were collected at baseline of 6 and 12 months. Dust samples were evaluated for dust mite, cockroach, mouse, and Alternaria by immunoassay. Air samples were evaluated for airborne mold spore concentrations. Overall, 89% of the children tested positive to ≥1 indoor allergen, with allergen-specific sensitivities ranging from 18% to 67%. Allergen concentration was associated with skin sensitivity for 1 of 10 environmental triggers analyzed (cat). Asthma symptom days did not differ with skin test sensitivity, and surprisingly, increased symptoms were observed in children whose baseline indoor airborne mold concentrations were below median levels. This association was not observed in follow-up assessments. The lack of relationship among allergen levels (including mold), sensitivities, and asthma symptoms points to the complexity of attempting to assess these associations during rapidly changing social and environmental conditions.